A single base pair substitution in zebrafish distinguishes between innate and acute startle behavior regulation. - Elelbin A Ortiz; Philip D Campbell; Jessica C Nelson; Michael Granato (PLoS ONE)
Behavioral thresholds define the lowest stimulus intensities sufficient to elicit a behavioral response. Establishment of baseline behavioral thresholds during development is critical for proper responses throughout the animal's life. Despite the relevance of such innate thresholds, the molecular mechanisms critical to establishing behavioral thresholds during development are not well understood. The acoustic startle response is a conserved behavior whose threshold is established during development yet is subsequently acutely regulated. We have previously identified a zebrafish mutant line (escapist) that displays a decreased baseline or innate acoustic startle threshold. Here, we identify a single base pair substitution on Chromosome 25 located within the coding sequence of the synaptotagmin 7a (syt7a) gene that is tightly linked to the escapist acoustic hypersensitivity phenotype. By generating animals in which we deleted the syt7a open reading frame, and subsequent complementation testing with the escapist line, we demonstrate that loss of syt7a function is not the cause of the escapist behavioral phenotype. Nonetheless, escapist mutants provide a powerful tool to decipher the overlap between acute and developmental regulation of behavioral thresholds. Extensive behavioral analyses reveal that in escapist mutants the establishment of the innate acoustic startle threshold is impaired, while regulation of its acute threshold remains intact. Moreover, our behavioral analyses reveal a deficit in baseline responses to visual stimuli, but not in the acute regulation of responses to visual stimuli. Together, this work eliminates loss of syt7a as causative for the escapist phenotype and suggests that mechanisms that regulate the establishment of behavioral thresholds in escapist larvae can operate independently from those regulating acute threshold regulation.